2000
DOI: 10.1001/archinte.160.8.1109
|View full text |Cite
|
Sign up to set email alerts
|

"Benign" Tumors and "Early Detection" in Mammography-Screened Patients of a Natural Cohort With Breast Cancer

Abstract: The results suggest that many of the breast cancers found by mammography screening have excellent prognosis not just because of early detection, but also because many of the cancers are relatively benign, requiring minimal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…4,5 Several studies have reported that, within stage, mammography-detected breast cancers have a more favorable prognosis than breast cancers detected with other methods, even after controlling for other available tumor characteristics. 2,3,6,7 These findings are consistent with a length time bias, in which slower growing tumors are more likely to be detected through mammography screening, and faster growing tumors are more likely to be detected clinically.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…4,5 Several studies have reported that, within stage, mammography-detected breast cancers have a more favorable prognosis than breast cancers detected with other methods, even after controlling for other available tumor characteristics. 2,3,6,7 These findings are consistent with a length time bias, in which slower growing tumors are more likely to be detected through mammography screening, and faster growing tumors are more likely to be detected clinically.…”
supporting
confidence: 69%
“…[1][2][3] Even among women who receive regular screening, cancers detected clinically in the interval between normal screening examinations (interval cancers) are more aggressive than those detected by screening. 4,5 Several studies have reported that, within stage, mammography-detected breast cancers have a more favorable prognosis than breast cancers detected with other methods, even after controlling for other available tumor characteristics.…”
mentioning
confidence: 99%
“…Women with breast cancer detected in mammography screening generally have more favorable outcome than those whose cancer is found outside of screening (1)(2)(3). Compared with cancers found by the patient herself, cancers detected in screening are usually smaller in size and are usually better differentiated and contain less tumor necrosis, have lower mitotic counts, express less frequently TP53 or HER2, have higher estrogen receptor (ER) and progesterone receptor (PR) contents, and are less frequently associated with regional lymph node metastases (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…In addition, it may also contribute to an increase in detection rates for slow-growing tumours that would have remained in the pre-clinical phase longer without screening mammography (Shen et al, 2005). Thus, breast cancer survivors are probably diagnosed more often and earlier with a low-grade breast cancer, which may require less aggressive treatment than other cancers (Moody-Ayers et al, 2000).…”
Section: Trend Of Breast Cancer In Female Cancer Survivors I Soerjomamentioning
confidence: 99%